Evaluation of the effect of dinoprostone vaginal ovule for cervical maturation and labor induction in term pregnancies on the duration of the third stage of labor and amount of postpartum bleeding: Evaluation of the effect of dinoprostone - Aytemiz , Emine; Çift , Tayfur; Aydın, Sakine Merve (Journal of Surgery and Medicine, 2023)
Background/Aim: Postpartum bleeding is a leading preventable cause of maternal death. Prolonged 3rd stage duration of labor and induction agents can increase postpartum bleeding. This study evaluated the effect of using a dinoprostone (PGE2) vaginal insert, a cervical ripening and labor induction agent, on the 3rd stage duration of labor and the amount of postpartum bleeding. Methods: This prospective cross-sectional study involved 301 patients with vaginal delivery between 01.10.2020 and 30.06.2021. Patients were separated into two groups: PGE2+oxytocin (Group A) and only oxytocin (Group B). They were compared in terms of prepartum and postpartum data, 3rd stage duration of labor, and the amount of blood loss in the first 18 h postpartum. Results: The median 3rd stage duration of labor was 8 min in Group A and 7 min in Group B (P=0.009). No significant differences were found between the groups in the amount of postpartum blood loss, percentage changes in hemoglobin and hematocrit values, or when patients were analyzed based on 3rd stage duration of labor (≤10 vs. >10 min). Severe postpartum hemorrhage (≥1000 ml) was associated with decreased gravida, increased body mass index, longer oxytocin use, and prolonged 3rd stage duration of labor in all patients. In Group A, severe postpartum hemorrhage was associated with decreased gravida, increased body mass index, and longer duration of PGE2 use. Conclusion: PGE2 prolonged the 3rd stage duration of labor, but this did not increase postpartum bleeding compared to oxytocin. However, an increase in the duration of PGE2 use was associated with postpartum hemorrhage. Therefore, shortening the duration may be considered in patients with additional risk for postpartum hemorrhage.